Evaluation of an electronic document management system implementation success from an end user perspective in an industrial company - Kuosmanen, Katariina (My University, 2019)
Most of the organizational information is stored in documents. Along with digitalization and global networks, the amount of information and electronic documents has increased massively. Electronic document management systems (EDMS) make it possible to manage the whole life cycle of a document, enhance document compliance, improve document visibility as well as to control and streamline processes electronically. This research investigated how implementation of the electronic document management system succeeded from an end user perspective in the case company. Success was defined to be the system users’ intention to use the system. Based on the previous literature, a new research model was developed to evaluate the user intention to use the newly implemented system and to figure out how different factors were related the intention. Data of the quantitative case study was used as an input for the research model. The data was collected with structured questionnaire from end users of the system in the industrial company. The questionnaire was generated on the basis of the research model which consisted of six research constructs: training, system characteristics, communication, ease of use, usefulness and intention to use. As a result, training and system characteristics were positively associated with perceived ease of use and perceived usefulness of the system. However, communication was not significantly related to perceived usefulness. Similarly, perceived ease of use was not positively associated with the intention to use the system. However, perceived ease of use was positively associated with the usefulness of the system. A useful system increased the intention to use the system which was defined to be the success in this research. All the research constructs had high mean value from respondents. Mean of 4.4/5 referred to as high commitment of the user’s intention to use the system and thus, it can be considered that the implementation was successful from the end user perspective. As a conclusion from the research, it is useful to put effort on training and system characteristics in the future implementations because those had the strongest impact on perceived ease of use and perceived usefulness of the system. If users feel that the system is easy to use it will increase the perceived usefulness of the system which will finally increase the intention to use the system.
Keywords: electronic document management system, EDMS, system implementation